PENDAMPINGAN UPGRADING PERPUSTAKAAN KUMALA DESA MAKMUR JAYA KECAMATAN KOMBENG - Amelia Putri; Tri Velyna; Widia Ningsih; Ajis Supangat; Febi Febrianti; Andini Idi; Ana Siti Parida Dwi Yuliantika; Erwin Saputra; Anna Tiara Rachma (P3M STAI Sangatta, 2026)
Village libraries, as one of the government's efforts to strengthen and develop outlying areas, are seen as being able to stimulate reading interest among rural communities. The construction of village libraries must be accompanied by the procurement or addition of existing book collections. This way, the goal of building village libraries can be achieved. One village that already has a village library is Makmur Jaya Village, Kombeng District. The Makmur Jaya Village Library is named the Kumala Library. It is hoped that with the provision of this library, the community's literacy skills will further develop. However, in reality, the management of the Kumala Library is still lacking. One of the work programs of group 8 KKL STAI Sangatta is upgrading the Kumala Library. The method used in this community service is the PAR (Participatory Action Research) method. The results of this community service show that there is mentoring that has a positive impact on the reading interest of the Makmur Jaya Village community.